Uso de antibióticos en pacientes hospitalizados en el Hospital Domingo Olavegoya de Jauja, periodo de julio a diciembre de 2024. - Poves Lino, Elizabeth Bertha; Torres Oropeza, José Luis (PE, 2026)
El objetivo del estudio fue describir el uso de antibióticos en pacientes hospitalizados en el Hospital Domingo Olavegoya de Jauja, periodo de julio a diciembre de 2024. Fue de tipo básico, no experimental, transversal y descriptivo. La muestra estuvo conformada por 219 historias clínicas entre Medicina y UCI mediante muestreo no probabilístico por conveniencia. Los resultados evidenciaron diagnósticos frecuentes J18.9 y R57.2, comorbilidad principal DM2 (7,8%), siendo el urocultivo el más solicitado, el 29,7% fueron cultivos positivos; en las cuales se aisló E. coli predominante, siendo sensible a amikacina. La ceftriaxona fue la más usada; predominó el grupo de Vigilancia (61,6%) y tratamiento empírico (71,7%). Se concluye que el uso de antibióticos fue mayormente empírico e inadecuado, evidenciando la necesidad de fortalecer el PROA.

The objective of this study was to describe antibiotic usage among patients hospitalized at the Domingo Olavegoya Hospital in Jauja during the period from July to December 2024. The study was basic in nature, non-experimental, cross-sectional, and descriptive. The sample consisted of 219 medical records from the Internal Medicine and ICU departments, selected via non-probabilistic convenience sampling. The results revealed frequent diagnoses of J18.9 and R57.2, with Type 2 Diabetes Mellitus (DM2) identified as the primary comorbidity (7.8%). Urine cultures were the most frequently requested diagnostic test, with 29.7% yielding positive results; *E. coli* was the predominant pathogen isolated in these cultures and was found to be susceptible to amikacin. Ceftriaxone was the most widely used antibiotic; the "Surveillance" category predominated (61.6%), as did empirical treatment (71.7%). It is concluded that antibiotic usage was predominantly empirical and inappropriate, thereby highlighting the need to strengthen the Antibiotic Stewardship Program (PROA).
Antibiotic Use in Hospitalized Patients at Domingo Olavegoya Hospital, Jauja: July to December 2024.
Keywords: Antibióticos; prescripción empírica; clasificación AWaRe; http://purl.org/pe-repo/ocde/ford#3.01.05